Fatigue of elbow flexors during repeated flexion-extension cycles: effect of movement strategy - Guevel, A.; Hogrel, J. Y.; Marini, J. F. (International Journal of Sports Medicine, 2000)
The objective of this work was to study the influence of movement strategy on fatigue of elbow flexors during repeated flexion-extension cycles in order to enlighten the fatigue process occurring during "pumping" in boardsailing. This dynamic exercise was performed by six high-level Olympic boardsailors according to two movement strategies with different amplitude and frequency. The parameters of the exercise were chosen to result in similar mechanical work at every instant for both modalities. Isometric evaluation was performed before and after dynamic exercise to quantify muscle fatigue. Analysis of physical parameters (maximum voluntary contraction, endurance time) and electromyographic parameters (in both temporal and frequency domains) emphasized the peripheral origin of muscle fatigue at the level of the biceps brachii and the brachioradialis. After considering the limitations of this type of study, the results are discussed in terms of synergy and differentiation between muscles, peripheral fatigue and movement strategy. Although the mechanical work and total physiological demands were similar for the two movement modalities, analysis of electromyographic parameters suggests that muscle fatigue mainly involves the biceps brachii when movements were slow and wide, and the brachioradialis when they were rapid and short. This study makes it possible to take these specificities into account in order to adjust the physical training program.